Decoding Tilism: AI, Translation, and the Transference of Cultural Narratives (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This paper explores the intersection of artificial intelligence (AI) with translation studies, focusing on the dynamics of translation and transference in cultural and literary contexts. Using Tilism-e-Hoshruba, a seminal work in Urdu dastan literature, as a case study, it examines how AI-driven translation tools navigate the complex interplay of language, culture, and narrative. The process of translation is not merely a linguistic act but a form of transference, carrying the nuances of identity, ideology, and context across cultural borders. The study highlights how AI-mediated translations, while efficient, grapple with capturing the layered richness of texts like Tilism-e-Hoshruba, where metaphors, idioms, and cultural symbols resist reduction to algorithms. By analyzing instances of successful and failed translations, the paper underscores the critical need for human-AI collaboration to preserve the integrity of literary works. This research contributes to a deeper understanding of the challenges and potentials of integrating AI into the field of literary translation, emphasizing the necessity of culturally aware and ethically grounded approaches.